2020
DOI: 10.1093/mnrasl/slaa010
|View full text |Cite
|
Sign up to set email alerts
|

A radio parallax to the black hole X-ray binary MAXI J1820+070

Abstract: Using the Very Long Baseline Array and the European Very Long Baseline Interferometry Network we have made a precise measurement of the radio parallax of the black hole Xray binary MAXI J1820+070, providing a model-independent distance to the source. Our parallax measurement of (0.348 ± 0.033) mas for MAXI J1820+070 translates to a distance of (2.96 ± 0.33) kpc. This distance implies that the source reached (15 ± 3) per cent of the Eddington luminosity at the peak of its outburst. Further, we use this distance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
161
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(183 citation statements)
references
References 38 publications
22
161
0
Order By: Relevance
“…The jet is then modeled by a truncated cone whose apex is at the central source, of 4 9 in height, 2 6 in width, and with an opening angle of 7°.1. Using 2.96 kpc as the distance to MAXIJ1820 +070 (Atri et al 2020), this corresponds to a volume of V= 1.4×10 51 cm 3 , and a jet of 1.5×10 4 au by 7.7 ×10 3 au, which is in accordance with the estimation performed by Bright et al (2020). Their estimate was obtained 40 days before by inferring it from radio flux comparisons, while we obtained directly a physical size using Chandra data.…”
Section: Energeticssupporting
confidence: 83%
See 2 more Smart Citations
“…The jet is then modeled by a truncated cone whose apex is at the central source, of 4 9 in height, 2 6 in width, and with an opening angle of 7°.1. Using 2.96 kpc as the distance to MAXIJ1820 +070 (Atri et al 2020), this corresponds to a volume of V= 1.4×10 51 cm 3 , and a jet of 1.5×10 4 au by 7.7 ×10 3 au, which is in accordance with the estimation performed by Bright et al (2020). Their estimate was obtained 40 days before by inferring it from radio flux comparisons, while we obtained directly a physical size using Chandra data.…”
Section: Energeticssupporting
confidence: 83%
“…The proper motions obtained with the ballistic fit mas day −2 . Assuming a distance of 2.96 kpc (Atri et al 2020), this corresponds to respective apparent initial velocities of 0.61c and 1.59c approximately. The superluminal apparent velocity of the south jet, which is much higher than the apparent velocity for the north jet, suggests that the south jet is the approaching component of the ejection while the north jet is the receding component.…”
Section: Motion Of the Jetsmentioning
confidence: 99%
See 1 more Smart Citation
“…These limits supersede the early restriction of 69 • i 77 • calculated by adopting an outer disk radius of R d ∼ 0.5R 1 and q 0.12 (Torres et al 2019). On one hand, the allowed range for i encloses those expected for an X-ray dipper binary (Frank et al 2002) and contains the 63 ± 3 • (1σ) inclination found for the radio jet (Atri et al 2020). On the other hand, it excludes the 29.8 +3.0 −2.7 • (3-σ) inclination for the inner disk obtained from modeling of X-ray spectra (Bharali et al 2019).…”
Section: Discussionsupporting
confidence: 51%
“…The black hole nature of the source was confirmed with a dynamical mass measurement by Torres et al (2019), who put the mass in the 7-8 M range. MAXI J1820+070 is a relatively nearby BH LMXB, with a distance of 2.96±0.33 kpc (Atri et al 2020), and it has low interstellar absorption (∼ 2 × 10 21 atoms cm −2 ; Kajava et al 2019). After spending roughly the first half of its 8 month outburst in the hard state, MAXI J1820+070 underwent a rapid state transition to the soft state in early July of 2018 (Homan et al 2018a,b).…”
Section: Introductionmentioning
confidence: 99%